Application of Electrical Resistivity Method in Designing a Structural Model for a Proposed Filling Station Site, Akure, Southwestern Nigeria (Global Journal of Science Frontier Research, 2017)
Abstract not found
Keywords: subsurface characterization; structural model; filling station